Spectrophotometric determination of formaldehyde with chromotropic acid in phosphoric acid medium assisted by microwave oven - Gigante, A. C.; Gotardo, M. A.; Tognolli, J. O.; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier B.V., 2004)
In the present study. a spectrophotometric method for the determination of formaldehyde by using chromotropic acid was devised. in which the use of potentially hazardous and corrosive concentrated sulfuric acid was eliminated and advantageously C replaced by a mixture of H, concentrated H3PO4 and H2O2. The reaction between formaldehyde and chromotropic acid (CA) in a cone phosphoric acid medium was accelerate by irradiating the mixture with microwave energy for 35 s (1100 W), producing a violetred compound (lambda(max)=570 nm). Beer's Law is obeyed in a concentration range of 0.8-4.8 mg 1(-1) of formaldehyde with a good correlation coefficient (r = 0.9968). The proposed method was applied in the analysis of formaldehyde in commercial disinfectants. Recoveries were within 98.0-100.4%, with standard deviations ranging from 0.03 to 0.13%. (C) 2003 Elsevier B.V All rights reserved.
Keywords: formaldehyde; chromotropic acid; spectrophotometry; microwave oven